Current issues of environmental management in Vietnam - the case of VEDAN Vietnam - Hoang, Van Hai (2016)
The theme of environmental management and sustainable economic development has attracted increasing attention of public organizations, businesses and citizens in Vietnam. However, the picture of sustainable development in Vietnam is unclear when we look into the current situation of illegal industrial waste missions by manufactures both inside and outside of industrial zones.